Detection of Common Arrhythmias by the Watch-PAT: Expression of Electrical Arrhythmias by Pulse Recording - Pillar G; Berall M; Berry RB; Etzioni T; Henkin Y; Hwang D; Marai I; Shehadeh F; Manthena P; Rama A; Spiegel R; Penzel T; et al. (Nature and Science of Sleep, 2022)
Giora Pillar,1 Murray Berall,2 Richard B Berry,3 Tamar Etzioni,1 Yaakov Henkin,4 Dennis Hwang,5 Ibrahim Marai,6,7 Faheem Shehadeh,6 Prasanth Manthena,8 Anil Rama,9 Rebecca Spiegel,10 Thomas Penzel,11 Riva Tauman12 1Sleep Laboratory, Carmel Medical Center and Technion Faculty of Medicine, Haifa, Israel; 2Center of Sleep and Chronobiology, University of Toronto, Toronto, ON, Canada; 3UF Health Sleep Center, University of Florida, Gainesville, FL, USA; 4Cardiology Department, Soroka Medical Center, Be’er Sheva, Israel; 5Kaiser Permanente San Bernardino County Medical Center, Fontana, CA, USA; 6Cardiology Department, Rambam Medical Center, Haifa, Israel; 7Baruch Padeh Medical Center and the Azrieli Faculty of Medicine in the Galilee, Poriya, Israel; 8Sleep clinic, Kaiser Permanente Los Angeles Medical Center, Los Angeles, CA, USA; 9Sleep Clinic, Kaiser Permanente San Jose Medical Center, San Jose, CA, USA; 10Department of Neurology and Sleep Center, Stony Brook University Hospital, Stony Brook, NY, USA; 11Charite Universitätsmedizin Berlin, Sleep Medicine Center, Berlin, Germany; 12Sleep Disorders Center, Tel Aviv Sourasky Medical Center and Sackler Faculty of Medicine, Tel Aviv University, Tel Aviv, IsraelCorrespondence: Giora Pillar, Sleep Laboratory, Carmel Medical Center and Technion Faculty of Medicine, Haifa, 31096, Israel, Tel +972 4 8250258, Fax +972 48250699, Email gpillar@technion.ac.ilBackground: The WatchPAT (WP) device was shown to be accurate for the diagnosis of sleep apnea and is widely used worldwide as an ambulatory diagnostic tool. While it records peripheral arterial tone (PAT) and not electrocardiogram (ECG), the ability of it to detect arrhythmias is unknown and was not studied previously. Common arrhythmias such as atrial fibrillation (AF) or premature beats may be uniquely presented while recording PAT/pulse wave.Purpose: To examine the potential detection of common arrhythmias by analyzing the PAT amplitude and pulse rate/volume changes.Patients and Methods: Patients with suspected sleep disordered breathing (SDB) were recruited with preference for patients with previously diagnosed AF or congestive heart failure (CHF). They underwent simultaneous WP and PSG studies in 11 sleep centers. A novel algorithm was developed to detect arrhythmias while measuring PAT and was tested on these patients. Manual scoring of ECG channel (recorded as part of the PSG) was blinded to the automatically analyzed WP data.Results: A total of 84 patients aged 57± 16 (54 males) participated in this study. Their BMI was 30± 5.7Kg/m2. Of them, 41 had heart failure (49%) and 17 (20%) had AF. The sensitivity and specificity of the WP to detect AF segments (of at least 60 seconds) were 0.77 and 0.99, respectively. The correlation between the WP derived detection of premature beats (events/min) to that of the PSG one was 0.98 (p< 0.001).Conclusion: The novel automatic algorithm of the WP can reasonably detect AF and premature beats. We suggest that when the algorithm raises a flag for arrhythmia, the patients should shortly undergo ECG and/or Holter ECG study.Keywords: home sleep apnea test, WatchPAT, obstructive sleep apnea, arrhythmia, atrial fibrillation